Properties and corrosion resistance mechanism of a self-healing octadecyl amine loaded ethyl cellulose microcapsule coatings loaded with epoxy resin - Qidong Cao; Shumei Kang; Chenshuo Lu; Dongpeng Sun; Jinghao Li; Hong Chen; Xintong Li (Scientific Reports)
Abstract In order to provide long-term anti-corrosion properties of the coatings on the substrate, a microcapsule self-healing coatings system was designed in this paper. Microcapsules were synthesized with ethyl cellulose and octadecyl amine, which were added to epoxy resin to prepare self-healing coatings. The shape of microcapsules was spherical, the average particle size of microcapsules was about 100–120 μm, and the average thickness of microcapsules was 4.43 μm, which was conducive to the preparation of the coatings. The initial evaporation temperature of the microcapsules was 165℃. The ethyl cellulose organic crosslinked shell enhances the strength of the microcapsules and improves the thermal stability of the microcapsules. Electrochemical impedance spectroscopy showed that the impedance of the coatings with 6 wt% microcapsules was about 2.68 × 106 Ω/cm2, which was 2 orders of magnitude higher than that of the coatings without microcapsules (5.23 × 104 Ω/cm2). Scanning electron microscope was used to observe the artificial scratches of the coatings for 24 h, and it was found that the microcapsule could repair the artificial scratches of the coatings well. The results showed that the addition of microcapsules can improve the anti-corrosion properties of the coatings.